2016
DOI: 10.4310/ajm.2016.v20.n5.a8
|View full text |Cite
|
Sign up to set email alerts
|

Yang–Mills–Higgs connections on Calabi–Yau manifolds

Abstract: Abstract. Let X be a compact connected Kähler-Einstein manifold with c 1 (T X) ≥ 0. If there is a semistable Higgs vector bundle (E , θ) on X with θ = 0, then we show that c 1 (T X) = 0; any X satisfying this condition is called a Calabi-Yau manifold, and it admits a Ricci-flat Kähler form [Ya]. Let (E , θ) be a polystable Higgs vector bundle on a compact Ricci-flat Kähler manifold X. Let h be an Hermitian structure on E satisfying the Yang-Mills-Higgs equation for (E , θ). We prove that h also satisfies the Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…To compute the Chern classes of E, we can replace it with the graded module associated to the filtration (5), i.e., we can assume that E is polystable and H-nflat. Then by the main result in [1] (Corollary 2.6), φ = 0. So E is actually numerically flat as a vector bundle, and then c i (E) = 0 [10].…”
Section: Filtering H-nflat Higgs Bundlesmentioning
confidence: 78%
See 2 more Smart Citations
“…To compute the Chern classes of E, we can replace it with the graded module associated to the filtration (5), i.e., we can assume that E is polystable and H-nflat. Then by the main result in [1] (Corollary 2.6), φ = 0. So E is actually numerically flat as a vector bundle, and then c i (E) = 0 [10].…”
Section: Filtering H-nflat Higgs Bundlesmentioning
confidence: 78%
“…where Q 1 and Q 2 are locally free and H-nflat and Q 1 is stable. By the snake Lemma we have 1 Actually that result was already contained in the proof Corollary 1.19 in [10].…”
Section: Filtering H-nflat Higgs Bundlesmentioning
confidence: 94%
See 1 more Smart Citation
“…The pattern continues in higher dimension, with Higgs bundles and co-Higgs bundles existing largely as general-type and Fano phenomena, respectively (see [Ra3,Co,B1,B2,BBGL]). Families of integrable co-Higgs bundles on Fano surfaces, namely P 2 and P 1 × P 1 , have been constructed in [Ra3,VC].…”
Section: Introductionmentioning
confidence: 99%
“…In [2] it was shown that the Higgs field of a polystable Higgs bundle over a simply connected Calabi-Yau manifold X necessarily vanishes. This result does not hold true in the semistable case, as the following example shows: take E = O X ⊕ Ω 1 X with Higgs field φ(f, ω) = (ω, 0).…”
Section: Introductionmentioning
confidence: 99%